Cr3C2-NiCr and WC-Ni thermal spray coatings as alternatives to hard chromium for erosion-corrosion resistance - Espallargas, N.; Berget, J.; Guilemany, J. M.; Benedetti, Assis Vicente [UNESP]; Suegama, P. H. (Elsevier B.V. Sa, 2008)
Cr3C2-NiCr and WC-Ni coatings are widely used for wear applications at high and room temperature, respectively. Due to the high corrosion resistance of NiCr binder, Cr3C2-NiCr coatings are also used in corrosive environments. The application of WC-Ni coatings in corrosive media is 14 not recommended due to the poor corrosion resistance of the (pure Ni) metallic matrix. It is well known that the addition of Cr to the metallic binder improves the corrosion properties. Erosion-corrosion performance of thermal spray coatings is widely influenced by ceramic phase composition, the size of ceramic particles and also the composition of the metallic binder. In the present work, two types of HVOF thermal spray coatings (Cr3C2-NiCr and WC-Ni) obtained with different spray conditions were studied and compared with conventional micro-cracked hard chromium coatings. Both as-sprayed and polished samples were tested under two erosion-corrosion conditions with different erosivity. Tungsten carbide coatings showed better performance under the most erosive condition, while chromium carbide coatings were superior under less erosive conditions. Some of the tungsten carbide coatings and hard chromium showed similar erosion-corrosion behaviour under more and less erosive conditions. The erosion-corrosion and electrochemical results showed that surface polishing improved the erosion-corrosion properties of the thermally sprayed coatings. The corrosion behaviour of the different coatings has been compared using Electrochemical Impedance Spectroscopy (EIS) and polarization curves. Total material loss due to erosion-corrosion was determined by weight loss measurements. An estimation of the corrosion contribution to the total weight loss was also given. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: erosion-corrosion; thermal spray; HVOF; hard chromium; WC-Ni; Cr3C2-NiCr